2d duality for orthogonal gauge theories with 8 supersymmetries - Eran Avraham; Oren Bergman (Journal of High Energy Physics, 2019)
Abstract We recently conjectured a set of dualities relating two-dimensional orthogonal gauge theories with N $$ \mathcal{N} $$ = (4, 4) supersymmetry, analogous to Hori’s dualities with N $$ \mathcal{N} $$ = (2, 2) supersymmetry. Here we provide a quantitative test of this conjecture by computing the elliptic genera of the dual pairs and showing that they agree. The elliptic genus of orthogonal gauge theories has multiple topological sectors that depend on the global structure of the group and on the value of a discrete θ parameter. We derive the dependence on the θ parameter by determining whether a given sector has (S)Pin structure or not.